Indoor apparent temperature, cognition, and daytime sleepiness among low‐income adults in a temperate climate. (9th December 2021) - Gronlund, Carina J.; Ketenci, Kaan Cem; Reames, Tony G.; Larson, Peter S.; Schott, Justin; Rowe, Zachary; Jenkins, Quinton S.; Sanca, Mario O.; Tournat, Troy; Sol, Ketlyne; Williams, Don'aa; Gijsbers, Emma; et al.
Abstract: The burden of temperature‐associated mortality and hospital visits is significant, but temperature's effects on non‐emergency health outcomes is less clear. This burden is potentially greater in low‐income households unable to afford efficient heating and cooling. We examined short‐term associations between indoor temperatures and cognitive function and daytime sleepiness in low‐income residents of Detroit, Michigan. Apparent temperature (AT, based on temperature and humidity) was recorded hourly in 34 participant homes between July 2019‐March 2020. Between July‐October 2019, 18 participants were administered word list immediate (WLL) and delayed (WLD) recall tests (10‐point scales) and the Epworth Sleepiness Scale (24‐point scale) 2–4 times. We applied longitudinal models with nonlinear distributed lags of temperature up to 7 days prior to testing. Indoor temperatures ranged 8–34°C overall and 15–34°C on survey days. We observed a 0.4 (95% CI: 0.0, 0.7) point increase in WLL and 0.4 (95% CI: 0.0, 0.9) point increase in WLD scores per 2°C increase in AT. Results suggested decreasing sleepiness scores with decreasing nighttime AT below 22°C. Low‐income Detroit residents experience uncomfortably high and low indoor temperatures. Indoor temperature may influence cognitive function and sleepiness, although we did not observe deleterious effects of higher temperatures.